Beyond rhythm: exploring infinite possibilities in music, movement and choreography-hands percussion Malaysia - Chan, Clare Suet Ching (Tanjong Malim, 2013)
Beyond rhythm: exploring infinite possibilities in music, movement and choreography-hands percussion Malaysia by Chan, Clare Suet Ching